Semantic Memory in HIV-associated Neurocognitive Disorders: An Evaluation of the "Cortical" Versus "Subcortical" Hypothesis. (28th September 2017) - Tierney, Savanna; Woods, Steven Paul; Verduzco, Marizela; Beltran, Jessica; Massman, Paul J; Hasbun, Rodrigo
Abstract: Objective: HIV-associated neurocognitive disorders (HAND) have historically been characterized as a subcortical condition that does not affect semantic memory; however, recent evidence suggests that the cortical regions that support semantic memory may be affected in HIV. Method: The current study examined the effects of HAND on semantic memory in 85 HIV+ individuals with HAND, 193 HIV+ individuals without HAND, and 181 HIV– individuals who completed the Boston Naming Test (BNT) and the Famous Faces subtest of the Kauffman Adolescent and Adult Intelligence Test (KAIT-FF). Results: Linear regressions revealed a significant adverse effect of HAND on total scores on the BNT and the KAIT-FF (all p s < .01). Analyses of BNT errors showed that individuals with HAND committed more semantically related errors as compared to the other two study groups (all p s < .05). However, there were no group differences in rates of visually based errors, which are more commonly observed in traditional subcortical diseases (all p s > .10). Conclusions: Results indicate that HAND may impose adverse effects on individuals' object naming and identification abilities suggestive of mild semantic deficits that parallel traditional cortical diseases such as Alzheimer's disease.